Aktivitas Ekstrak Etanol Kulit Apel Hijau (Pyrus malus L.) Sebagai Agen Antiproliferatif Sel Kanker Payudara T47D - Bagas Herbayu Adhitya; Devi Nisa Hidayati Nisa (Farmasains : Jurnal Ilmiah Ilmu Kefarmasian, 2025)
Quercetin, a flavonoid compound in green apple peel (Pyrus malus L.), has shown anticancer potential in T47D cells. This study evaluated the cytotoxic effects and antiproliferative activities demonstrated by the Ethanolic Extract of Green Apple Peel (EEGAP) on T47D cells. The peel powder was extracted using 70% ethanol with ultrasonic waves. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was performed for the cytotoxicity test using EEGAP concentrations of 31.25, 62.5, 125, 250, 500, and 1,000 µg/mL. The IC50 value was determined using probit analysis. Based on the IC50 results, an antiproliferative assay was conducted using the doubling time technique at concentrations of ½IC50 (404.5 µg/mL) and IC50 (809 µg/mL), which were observed at 0, 24, 48, and 72 hours. EEGAP has a moderate cytotoxic effect, with an IC50 value of 809 µg/mL. EEGAP showed significant antiproliferative activity, with a doubling time of 14 hours in control samples. EEGAP at a concentration of ½ IC50 showed a replication period of 21 hours, whereas the IC50 concentration replication period was 30 hours. These results suggest that EEGAP exhibits cytotoxic and antiproliferative properties, which may have potential as a natural compound for breast cancer therapy.